Political Awakenings - Claudia Franziska Brühwiler (Transatlantica)
Philip Roth’s The Plot Against America traces the political awakening of its two child protagonists, the narrator Philip and his elder brother Sanford. While the latter undergoes an initiation process nearly in accordance with the classical tripartite scheme as coined by van Gennep, the height of Philip’s initiation process is marked by physical pain and injury. However, both experience only a partial initiation, since the elder brother will have to recognize his errors and the younger one will first have to learn how to go beyond the mere questioning of authority.